Study of tissue inflammatory response in different mice strains infected by dematiaceous fungi Fonsecaea pedrosoi - Marilia Marufuji Ogawa; Mario Mariano; Maria Regina Regis Silva; Milvia Maria Simões e Silva Enokihara; Nilceo Schwery Michalany; Angela Satie Nishikaku; Agenor Messias Silvestre; Jane Tomimori (Sociedade Brasileira de Dermatologia, 2019)
Abstract: Background: Diseases caused by melanized fungi include mycetoma, chromoblastomycosis and phaeohyphomycosis. This broad clinical spectrum depends on the dynamic interactions between etiologic agent and host. The immune status of the host influences on the development of the disease, as, an exemple. phaeohyphomicosis is more frequently observed in immunocompromised patients. Objectives: Examine the histological inflammatory response induced by Fonsecaea pedrosoi in several different strains of mice (BALB/c, C57BL/6, Nude and SCID, and reconstituted Nude). Methods: Fonsecaea pedrosoi was cultivated on agar gel and a fragment of this gel was implanted subcutaneously in the abdominal region of female adult mice. After infection has been obtained, tissue fragment was studied histopathologically. Results: There were significant changes across the strains, with the nodular lesion more persistent in Nude and SCID mice, whereas in immunocompetent mice the lesion progressed to ulceration and healing. The histopathological analysis showed a significant acute inflammatory reaction which consisted mainly of neutrophils in the initial phase that was subsequently followed by a tuberculoid type granuloma in immunocompetent mice. Study limitations: There is no a suitable animal model for chromoblastomycosis. Conclusions: The neutrophilic infiltration had an important role in the containment of infection to prevent fungal spreading, including in immunodeficient mice. The fungal elimination was dependent on T lymphocytes. The re-exposure of C57BL/6 mice to Fonsecaea pedrosoi caused a delay in resolving the infection, and appearance of muriform cells, which may indicate that re-exposure to fungi, might lead to chronicity of infection.